Hybridization Of Human And Technics As Transformation Of The Border Of Corporeality: In The Context Of Biomedical Ethics - Місержи, С. Д. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction. The medical practices of hybridization of human beings and technics have renewed the discussions on essence of human, permissible interference in human nature. The aim and tasks. The aim of article is to identify a complex of bioethical problems arising from the splicing of the human body and non-biological technical components in the field of medicine. Research methodology. The interdisciplinary research requires a set of philosophical and general scientific methods that provide analysis of processes at the boundary of medicine, technology and society. Research results. There are two polar approaches to the problem of hybridization of human and technology in medicine: the first, the need to maximize human life by interfering human natural parameters by using biological and non-biological carriers is advocated; second one deals with religious restrictions on such experiments. The introduction of the concept of corporeality is associated with the search for a productive category of analysis of human nature through overcoming the dichotomy of subject-object, body-soul, physical-ideal. Philosophical and cultural studies consider corporeality as included in the sociocultural space "physical body", which under the influence of sociocultural determinants acquires new properties and acts as corporeality. Discussion. The systems to diagnose and maintain human life support, bionic prostheses, cardio implants, implants for restoration of vision and hearing, neurocomputer interfaces and more are often used among many types of body and non-biological components. As the development of a non-biological object that deforms the boundaries of the body, its appropriation occurs; subjectivity and the boundary of corporeality are shifted. However, society is not always ready to accept changes and there may be medical stigma. Conclusions. Concepts such as cyborgization, bionics, transhumanism, the sinister valley effect (ultimately bioethics and biomedical ethics) are an attempt to make sense of the growing importance in human life of decisions based on the acceptance / rejection of objects (models) of the interaction of biological and non-biological components. Society must determine in which system of value coordinates these relations will be governed.